2012
DOI: 10.1007/s00432-012-1149-7
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of elevated vascular endothelial growth factor in patients with osteosarcoma: a meta-analysis and systemic review

Abstract: The prognostic significance of VEGF expression in all its isoforms is still unknown based on the limited data available, but we find VEGF165 may play an important role. Future studies should examine the relationship between VEGF isoform expression and patients' survival and the relationship between VEGF isoform expression and EMMPRIN expression, which could be helpful for predicting the prognosis of patients with osteosarcoma. Once the conclusion of whether the VEGF and its isoforms playing a role in osteosarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 22 publications
(43 reference statements)
2
18
0
2
Order By: Relevance
“…As one of the most common primary malignant bone tumors in the world, osteosarcoma is a highly malignant mesenchymal-based tumor that mainly presents in children and teenagers [1, 2]. The annual morbidity of osteosarcoma is approximately 5 million cases worldwide [3] with prevalence towards males at a ratio of 1.5 : 1.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most common primary malignant bone tumors in the world, osteosarcoma is a highly malignant mesenchymal-based tumor that mainly presents in children and teenagers [1, 2]. The annual morbidity of osteosarcoma is approximately 5 million cases worldwide [3] with prevalence towards males at a ratio of 1.5 : 1.…”
Section: Introductionmentioning
confidence: 99%
“…Inducing angiogenesis is one of the hallmarks of cancer (Hanahan et al, 2011) , and VEGF, as one of the most important regulators in tumor angiogenesis (Ferrara, 2004), has been thought to be valuable of predicting poor outcome of survival in several cancers, such as lung cancer (Zhan et al, 2009), hepatocellular carcinoma (Schoenleber et al, 2009), gastric cancer (Chen et al, 2011), ovarian cancer (Yu et al, 2012), and osteosarcoma (Qu et al, 2012). However, the prognostic value of VEGF in bladder cancer was undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that VEGF (Qu et al, 2012) and HER-2 (Li and Geng, 2010) were not significantly associated with prognosis in human osteosarcoma, whereas TP53 (Pakos et al, 2004) and P-glycoprotein (Pakos and Ioannidis, 2003) were significantly associated with prognosis in patients with osteosarcoma. However, besides our study, these meta-analyses consider Ezrin positivity was associated with a lower 2-year survival rate.…”
Section: Meta-analysis On Ezrin Gene Associations With Response To Chmentioning
confidence: 75%
“…Recently, many meta-analyses have been performed to investigate the association between many genes (VEGF (Qu et al, 2012), HER-2 (Li and Geng, 2010), TP53 (Pakos et al, 2004), P-glycoprotein (Pakos and Ioannidis, 2003) et al) and prognosis in patients with osteosarcoma. The results indicated that VEGF (Qu et al, 2012) and HER-2 (Li and Geng, 2010) were not significantly associated with prognosis in human osteosarcoma, whereas TP53 (Pakos et al, 2004) and P-glycoprotein (Pakos and Ioannidis, 2003) were significantly associated with prognosis in patients with osteosarcoma.…”
Section: Meta-analysis On Ezrin Gene Associations With Response To Chmentioning
confidence: 99%